The Impact of Assisted Reproductive Technology in Twin Pregnancies Complicated by Intrahepatic Cholestasis of Pregnancy: a Retrospective Cohort Study - Çelik, Samettin; Çalışkan, Canan (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Introduction Our study aims to evaluate the perinatal outcomes in twin pregnancies diagnosed with intrahepatic cholestasis of pregnancy (ICP) and to compare these with normal healthy twin pregnancies for perinatal outcomes. The second outcome of the study was to determine whether in vitro fertilization-embryo transfer (IVF-ET) affects the perinatal outcome in ICP patients.Materials and Methods In this study, 59 ICP and 641 healthy twin pregnancies were compared for perinatal outcomes retrospectively. According to the mode of conception, the twin pregnancies with ICP were divided into 2 groups. The twin pregnancies with ICP who were conceived with IVF were referred to as the IVF-ET group. The twin pregnancies with ICP who were conceived spontaneously or by ovulation induction and intrauterine insemination (IUI) were referred to as the non-IVF-ET group.Results Twin pregnancies with ICP give birth significantly earlier than normal twin pregnancies (p ˂ 0.001). The diagnosis of ICP occurred significantly earlier in the IVF-ET pregnancy with ICP than in the non-IVF-ET group. In twin pregnancies with IVF-ET, patients delivered significantly earlier than in the non-IVF-ET group (p=0.002). Twin pregnancies with ICP were found to have significantly higher rates of meconium-stained amniotic fluid, postnatal intubation, and admission to the neonatal intensive care unit (NICU) than healthy twin pregnancies.Conclusions ICP is a risk factor for preterm delivery in twin pregnancies. In addition, ICP develops earlier and more frequently in twin pregnancies from IVF-ET than in those from non-IVF twin pregnancies, and the disease may be more serious.
Keywords: Intrahepatic Cholestasis of Pregnancy; Twin Pregnancy; In-Vitro Fertilization- Embryo Transfer